Spatial Patterns on Traditional Houses in Java as an Effort to Preserve Historic Buildings - Johan Wahyudi; Pindo Tutuko; Hery Budiyanto (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Java Island can be divided into several cultural areas of Banten and Sunda in West Java, while in Central Java and East Java there are Pesisir Kilen, Pesisir Wetan, Banyumas, Bagelen, Negarigung, Mancanegari, Surabaya, Tanah Sabrang Wetan and Madura (Koentjaraningrat 1994: 27). Traditional buildings have been a silent witness to how life in the past was run and its influence on the life order of society at that time and has the original building characteristics of Indonesian society in that era and functionally have special purpose and purpose which influence the process of the establishment of the building. This study is expected to provide a benefit form of development of science related to traditional houses in general that can be applied in building architecture. The method used in this paper is the study description descriptions, namely exposing and analyzing spatial patterns in some traditional houses in Java. The method of data collection is done by looking for literature studies on the issues to be discussed, namely the literature of several studies that have been done and has been published in the form of scientific papers. From the discussion of the pattern of space to some traditional houses on the island of Java, there are similar patterns, although in the arrangement of space there is in one mass of buildings and mass plural.